A comparative study of volatile flavor components in four types of zaoyu using comprehensive two‐dimensional gas chromatography in combination with time‐of‐flight mass spectrometry. Issue 3 (21st January 2021) - Chen, Zhipeng; Tang, Haiqing; Ou, Changrong; Xie, Cheng; Cao, Jinxuan; Zhang, Xin
Abstract: Volatiles of four zaoyu (Chinese traditional fermented fish) products prepared from different species of marine fish were analyzed by headspace solid‐phase micro‐extraction (HS‐SPME) and comprehensive two‐dimensional gas chromatography in combination with time‐of‐flight mass spectrometry (GC × GC/TOFMS). First, a 50/30 µm DVB/CAR/PDMS was used and the influence of several parameters on the efficiency of HS‐SPME such as extraction temperature, time, salting‐out effect, and stirring were optimized, odor activity values (OAVs) of volatile compounds were computed based on the threshold values of aroma constituents; the characteristic volatiles and their odor characteristics of the four zaoyu were investigated. The results demonstrated that the most effective extraction of the analytes was obtained with a 40 min extraction at 50°C with the addition of 20% NaCl and stirring at 300 r/min. Under these conditions, a total of 288 volatile components were tentatively identified based on mass spectra and comparison of linear retention indices in the four zaoyu products. Authenticated compounds included aldehydes, esters, alcohols, ketones, furans, lactones, nitrogen compounds, sulfur compounds, terpenes, phenols, etc. Among the identified types of volatile compounds, the number of esters is the largest, whereas the content of aldehydes is the highest. The results of OAVs comparisons proved that both aldehydes and esters provided the most significant contribution to the aromas of zaoyu, and each zaoyu product had its own unique active flavor components. Moreover, the OAVs of active flavor compounds common to the four examined zaoyu varied significantly. Our results substantiated that GC × GC/TOFMS could provide a robust technical means to understand the flavor characteristics of zaoyu and allow us to better evaluate and improve the flavor quality of the products with complex food matrix like zaoyu. Practical applications: The method present in this research is suitable to characterize the volatile constituents of aquatic products, and could also be used for component characterization of similar complex samples such as fermented fish and foods. Understanding the key aroma compounds of fermented fish and its formation mechanism could provide a guide of process optimization and flavor regulation, contributing to further studies related to volatile compounds in the field of food flavor analysis.